Differential Morphological Diagnosis of Various Forms of Congenital Hyperinsulinism in Children - Mitrofanova, Lubov Borisovna; Perminova, Anastasia Arkadyevna; Ryzhkova, Daria Viktorovna; Sukhotskaya, Anna Andreyevna; Bairov, Vladimir Gireyevich; Nikitina, Irina Leorovna (Frontiers in Endocrinology, 2021)
Congenital hyperinsulinism (CHI) has diffuse (CHI-D), focal (CHI-F) and atypical (CHI-A) forms. Surgical management depends on preoperative [18F]-DOPA PET/CT and intraoperative morphological differential diagnosis of CHI forms. Objective: to improve differential diagnosis of CHI forms by comparative analysis [18F]-DOPA PET/CT data, as well as cytological, histological and immunohistochemical analysis (CHIA). Materials and methods. The study included 35 CHI patients aged 3.2±2.0 months; 10 patients who died from congenital heart disease at the age of 3.2±2.9 months (control group). We used PET/CT, CHIA of pancreas with antibodies to ChrA, insulin, Isl1, Nkx2.2, SST, NeuroD1, SSTR2, SSTR5, DR1, DR2, DR5; fluorescence microscopy with NeuroD1/ChrA, Isl1/insulin, insulin/SSTR2, DR2/NeuroD1 cocktails. Results. Intraoperative examination of pancreatic smears showed the presence of large nuclei, on average, in: 14.5±3.5 cells of CHI-F; 8.4±1.1 of CHI-D; and 4.5±0.7 of control group (from 10 fields of view, x400). The percentage of Isl1+ and NeuroD1+endocrinocytes significantly differed from that in the control for all forms of CHI. The percentage of NeuroD1+exocrinocytes was also significantly higher than in the control. The proportion of ChrA+ and DR2+endocrinocytes was higher in CHI-D than in CHI-F, while the proportion of insulin+cells was higher in CHI-A. The number of SST+cells was significantly higher in CHI-D and CHI-F than in CHI-A. Conclusion. For intraoperative differential diagnosis of CHI forms, quantitative cytological analysis is the most optimal. In quantitative immunohistochemistry, CHI forms differ in the expression of ChrA, insulin, SST and DR2. The development of a NeuroD1 inhibitor would be advisable for targeted therapy of CHI.